Benchmarking leachate co-treatment strategies in municipal wastewater treatment plants under dynamic conditions and energy prices. (15th April 2020) - Dereli, Recep Kaan; Giberti, Matteo; Liu, Qipeng; Flynn, Damian; Casey, Eoin
Abstract: Combined leachate treatment at municipal wastewater treatment plants (WWTPs) is applicable to a certain extent depending on the leachate composition, treatment plant configuration and its capacity. Co-treatment of leachate at WWTPs has several advantages, but due to increasingly stringent discharge standards applied in WWTPs, it has become more problematic. This study was undertaken to investigate the impact of leachate feeding strategies on effluent quality and the aeration energy costs of WWTPs. A modified version of Benchmark Simulation Model No.1 was used to develop, test and compare several leachate feeding and WWTP control strategies in the context of dynamic pollutant loads and energy prices. The results highlighted that combined leachate treatment led to a deterioration in the quality of discharged wastewater, as indicated by a 12–20% increase in effluent quality index. Additionally, it adversely affected aeration energy demand and cost of the plant by increasing them 1.7–2.3% and 0.8–2.5%, respectively. The impacts could be mitigated by adjusting leachate flow based on effluent ammonium concentrations and by using advanced process control, i.e. feedback ammonium control for dissolved oxygen regulation in aerobic reactors. The study demonstrates that modeling can be used as a valuable tool to assess the potential impacts of leachate co-treatment and develop better management strategies. Graphical abstract: Image 1 Highlights: BSM1 model was used to investigate leachate co-treatment strategies in WWTPs. Six scenarios, i.e. shock and drip leachate feeding, were tested under dynamic conditions. Effluent quality index deteriorated by 12–20% for different feeding regimes. Aeration energy costs increased by 0.8–2.5% under a variable electricity price tariff. Aeration cost was reduced by 1.6% by using NH4 based feeding and DO control strategy.